Perempuan dan Media: Perempuan Salafi dan Aksesibilitas Media (Studi Etnografi Pada Perempuan Salafi di Wisma Qaanitah, Yogyakarta) - , FIRZA SABRINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the process or system of communication, access refers to the possibility for the sender of the message to reach the audiences that they choose or for the audience to accept a particular message or specific channel. Access to the media is not a question about how often, but it is the question of how the media accessibility can be meaningful in the human life. One of the internet characteristic that different from the other media is that the Internet could be best in personal use. The use of the media is rated from the perspective of the individual in which the Internet becomes the medium they choose to perform their goals. In short, Salafi is the people who attribute themselves to the methodology of the Salaf. Salaf is not a class or a group, but it is a manhaj. On the opinion of the shalafush Salih, women are required to wear the hijab to the rest of their body except the face and palms. Salafi women practicing this as a form of obedience to Allah's command and to be able to practice their believing in Islam. We can not close our eyes that the women of Salafis are also access the mainstream media. However, the intensity of those in the media access vary depending on the level of their needs. It is as in the Wisma Qaanitah, Yogyakarta. Wisma Qaanitah is a muslimah place, most of them are students. The majority of women in the Wisma Qaanitah Salafi wearing a chador/purdah in daily life. They access the media just like other women in general, but they tend to access media content related to the Salaf. The use of television were not allowed in Wisma, but it can not stop them from the access of the other media. Paid wifi and cellular phones that can be used for the internet, making them able to access the internet with these ease. By using the ethnographic method, Uses and Gratification Theory, researcher is trying to see the media accessibility conducted by the Salafi women in Wisma Qaanitah. As in this study will raise the issue of audience behavior by Salafi veiled women in accessing the media.